2020
DOI: 10.1055/a-1132-5544
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Iodine Concentrations on Patient-Reported Discomfort in Contrast-Enhanced Computed Tomography: A Prospective Comparative Trial

Abstract: Purpose Reducing contrast media injection speed while maintaining iodine flux is a promising workaround to lower or avoid contrast media-related discomfort during CT examinations. This approach demands contrast media with a higher concentration to guarantee excellent image quality. It remains unclear whether these concentration changes affect the patient’s experience. Thus, the aim of this study was to evaluate the influence of different concentrations of intravenous iodinated contrast media on patient discomf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In addition, previous research found conflicting results examining the effect of CM viscosity on heat and pain sensation. 20,22 Furthermore, these studies reported that the results that were significant, indicating that low concentrated CM is preferable over high concentrated CM in terms of pain and heat sensation, were small and not of clinical relevance. Hence, it is likely that differences in CM concentration do not have a significant impact on heat or pain sensation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, previous research found conflicting results examining the effect of CM viscosity on heat and pain sensation. 20,22 Furthermore, these studies reported that the results that were significant, indicating that low concentrated CM is preferable over high concentrated CM in terms of pain and heat sensation, were small and not of clinical relevance. Hence, it is likely that differences in CM concentration do not have a significant impact on heat or pain sensation.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still diversity in the literature concerning these topics. [14][15][16][17][18][19][20][21][22][23][24] The viscosity of CM can be reduced by lowering the CM concentration or by elevating its temperature. 16,17,25,26 Various studies have presented differing perspectives on the impact of CM concentration on patient comfort, safety, and image quality, yielding inconsistent results.…”
mentioning
confidence: 99%
See 3 more Smart Citations